Denmark : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
The global financial crisis hit Denmark hard, and the recovery has been slow and unsteady. Denmark's slow growth predates the recent economic crisis, and the economy has underperformed its regional peers. The current account remains in surplus, largely reflecting weak domestic demand since the crisis and strong net income. Monetary policy is based on maintaining a tight peg to the euro. Denmark's financial system has rebuilt capital but still has substantial vulnerabilities. Potential growth is expected to recover gradually.